Design the invention of desire - Helfand, Jessica (Yale University Press, 2016)
Design has always prided itself on being relevant to the world it serves, but interest in design was once limited to a small community of design professionals. Today, books on "design thinking" are best sellers, and computer and Web-based tools have expanded the definition of who practices design. Looking at objects, letterforms, experiences, and even theatrical performances, award-winning author Jessica Helfand asserts that understanding design's purpose is more crucial than ever. Design is meaningful not because it is pretty but because it is an intrinsically humanist discipline, tethered to the very core of why we exist. For example, as designers collaborate with developing nations on everything from more affordable lawn mowers to cleaner drinking water, they must take into consideration the full range of a given community's complex social needs. Advancing a conversation that is unfolding around the globe, Helfand offers an eye-opening look at how designed things make us feel as well as how-and why-they motivate our behavior